The Influence of Discipline, Motivation, and Communication on Job Satisfaction of Teachers at SMK Negeri 1 Balikpapan - afni asmaningsih; Hasan, Syahril; Yuliani, Tutik (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2025)
Afni Asmaningsih (2025). The Influence of Discipline, Motivation, and Communication on Job Satisfaction of Teachers at SMK Negeri 1 Balikpapan. Supervisors: Mr. Syahril Hasan and Mrs. Tutik Yuliani. This study aims to determine the effect of Discipline, Motivation, and Communication on Teacher Job Satisfaction at SMK Negeri 1 Balikpapan. This study uses a quantitative type with a sampling technique using purposive sampling. Data were collected through questionnaires and analyzed using SmartPLS software. The results showed that Discipline did not have a partial effect on job satisfaction, Motivation did not have a partial effect on job satisfaction, and Communication had a partial effect on teacher job satisfaction at SMK Negeri 1 Balikpapan. Keywords: Discipline, Motivation, Communication, Job Satisfaction